Penerapan Sistem Manajemen Persediaan Bahan Baku untuk Menekan Inventory Cost Menggunakan Metode Economic Order Quantity - Silalahi, Ira Valentina; Halim, Asep Abdul (Jurnal Maps (Manajemen Perbankan Syariah), 2021)
PT. Inkomas Lestari is the first and only producer from Indonesia to produce tin chemicals and polymer additives. The products produced by PT. Inkomas Lestari is not only able to meet the needs of the local market, but also meet the needs of the international market by exporting its products to Germany, Korea, China and several countries in the Asian region. However, based on the results of the evaluation conducted by researchers, PT. Inkomas Lestari is known to not optimize its inventory management, in which the company does not keep stock of raw material inventory in the warehouse, so that it often experiences an increase in inventory costs. This research was conducted with the aim of reducing inventory costs by calculating the safety stock needed by the company using the Economic Order Quantity (EOQ) method. Based on the calculation results, it is known that PT. Inkomas Lestari with the EOQ method obtained a total inventory cost of Rp. 1,888,637,963 which is lower than the company using the conventional method which has to pay Rp. 2,112,320,822, then with a difference in total inventory cost of Rp. 223,682,857. This means that the Economic Order Quantity (EOQ) method can be considered more efficient than the conventional method currently being applied by the company.